Countering online propaganda and extremism the dark side of digital diplomacy - Bjola, Corneliu; Pamment, James (London New York Routledge, 2019)
"Exploring the 'dark side' of digital diplomacy, this volume highlights some of the major problems facing democratic institutions in the West and provides concrete examples of best practice in reversing the tide of digital propaganda"--
Propaganda as reflexive control: the digital dimension / Corneliu Bjola -- Information influence in western democracies: a model of systemic vulnerabilities / Howard Nothhaft, James Pamment, Henrik Agardh-Twetman, Alicia Fjällhed -- A digital ménage à trois : strategic leaks, propaganda and journalism / Emma L. Briant, Alicia Wanless -- The use of political communication by international organisations : the case of EU and NATO / Eva-Karin Olsson, Charlotte Wagnsson And Kajsa Hammargård -- The unbearable thinness of strategic communication / Cristina Archetti -- The democratisation of hybrid warfare and practical approaches to defeat violent extremism in the digital age / Alicia Kearns -- The aesthetics of violent extremist and counter violent extremist communication / Ilan Manor, Rhys Crilley -- Virtual violence : understanding the potential power of ISIS- violent videos to buttress strategic narratives and persuade foreign recruits / Sean Aday -- The battle for the battle of the narratives : sidestepping the double fetish of digital and CVE / Akil Awan, Alister Miskimmon, Ben O'Loughlin --Conclusion : rethinking strategic communication in the digital age / James Pamment And Corneliu Bjola.
Includes bibliographical references (pages 181-209) and index.
Keywords: Extremist Web sites; Information warfare; Internet and international relations; Mass media and international relations; Mass media and propaganda; Propaganda, International; Internet -- Political aspects; Social media -- Political aspects